Mercury Exposure and Its Health Effects in Workers in the Artisanal and Small‐Scale Gold Mining (ASGM) Sector—A Systematic Review - Taux, Kira; Kraus, Thomas; Kaifie, Andrea (International Journal of Environmental Research and Public Health, 2022)
Gold is one of the most valuable materials but is frequently extracted under circumstances that are hazardous to artisanal and small‐scale gold miners’ health. A common gold extraction method uses liquid mercury, leading to a high exposure in workers. Therefore, a systematic review according to the PRISMA criteria was conducted in order to examine the health effects of occupational mercury exposure. Researching the databases PubMed®, EMBASE® yielded in a total of 10,589 results, which were screened by two independent reviewers. We included 19 studies in this review. According to the quantitative assessment, occupational mercury exposure may cause a great variety of signs and symptoms, in particular in the field of neuro‐psychological disorders, such as ataxia, tremor or memory problems. However, many reported symptoms were largely unspecific, such as hair loss or pain. Most of the included studies had a low methodological quality with an overall high risk of bias rating. The results demonstrate that occupational mercury exposure seriously affects miners’ health and well‐being.Ôand Web of Science.
CRIS-Team Scopus Importer:2023-09-25
Keywords: Disease; Health; Heavy metal; Intoxication; Neuro‐psychological disorders; Work